Clinical outcomes of early vs. late extubation following cardiac surgery: a systematic review and meta-analysis - Mohammad S. Dairi; Husna Irfan Thalib; Sariya Khan; Ayesha Jamal; Saeed M. Alghamdi; Abdulelah M. Aldhahir; Abdullah A. Alqarni; Tope Oyelade; Imran Khalid; Sultan Salem Bawazeer; Amir Aziz; Hassan Alwafi (Frontiers in Medicine, 2026)
Objective This systematic review and meta-analysis evaluated clinical outcomes associated with earlier vs. later extubation in adults undergoing cardiac surgery. Methods A systematic review and meta-analysis were conducted following PRISMA guidelines, with the study registered in PROSPERO. We searched PubMed, Scopus, Web of Science, CENTRAL, and EBSCO from inception until April 2025. Two reviewers independently screened studies. We included observational and interventional studies comparing early vs. late extubation following cardiac surgery in adult patients. Primary outcomes were all-cause mortality, length of intensive care unit (ICU) stay, length of hospital stay, reintubation, postoperative pneumonia, and postoperative renal failure requiring continuous renal replacement therapy (CRRT). Secondary outcomes included mediastinal bleeding requiring re-exploration, tracheostomy, and hospital or ICU readmission. Risk of bias in randomized trials was assessed using the Cochrane Risk of Bias tool, while the Newcastle-Ottawa Scale (NOS) was used for observational studies. Data synthesis was performed using Review Manager version 5.4. For continuous outcomes, pooled effect estimates were expressed as mean differences (MDs). For dichotomous outcomes, pooled odds ratios (ORs) with corresponding 95% CIs were calculated. Random-effects models were used as the primary analysis. A subgroup analysis based on extubation threshold ( ≤ 6 h or >6 h) was conducted. Statistical heterogeneity was assessed using the Chi-square test and the I 2 statistic. Results A total of 237 records were identified, of which only 19 studies (18 observational and one randomized trial) were included in this meta-analysis. Earlier extubation was associated with lower odds of mortality (OR 0.09, 95% CI 0.04–0.23), reintubation (OR 0.22, 95% CI 0.07–0.70), postoperative pneumonia (OR 0.20, 95% CI 0.09–0.45), renal failure requiring CRRT (OR 0.10, 95% CI 0.06–0.17), postoperative tracheostomy (OR 0.01, 95% CI: 0.00–0.03), and hospital or ICU readmission (OR 0.25, 95% CI 0.07–0.86). Conclusions In adults undergoing cardiac surgery, earlier extubation was associated with favorable postoperative outcomes including lower mortality, shorter ICU and hospital stays, and lower rates of reintubation, postoperative pneumonia, tracheostomy, CRRT, and hospital or ICU readmission. However, future randomized trials and prospective studies are warranted as the available evidence was predominantly observational and clinically heterogeneous. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420261361735 , identifier: CRD420261361735.